COMPANY CHARACTERISTICS, PERFORMANCE, AND DISCLOSURE OF HUMAN RESOURCE ACCOUNTING: EMPIRICAL STUDY OF BANKING COMPANIES IN INDONESIA - Sri Kusumastuti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The process of identifying and measuring human resource data and transmitting this information to interested parties is human resource accounting. Financial reporting from external HR accounting can play an important role in helping to properly manage the HR of an organization. This research aims to analyze the impact of the performance of the company and company on disclosures of human resource accounting. The data method uses secondary data and multiple regression analysis is used in the data analysis method. The results of the analysis show that the size of the business, leverage, CAR, and LDR have a positive and significant impact on the disclosure of human resource accounting. Company age and profitability, meanwhile, have no significant impact on the disclosure of human resource accounting. The theoretical contribution to this research is to analyze the company's assessment and performance simultaneously with regard to the disclosure of human resource accounting in Indonesian banking companies.